1995
DOI: 10.3181/00379727-208-43844
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Antipromotional Effects of the Soybean Isoflavone Genistein

Abstract: Antioxidant and antipromotional effects of the soybean isoflavone genistein have been studied in HL-60 cells and the mouse skin tumorigenesis model. Effects of structure-related flavone/isoflavones on hydrogen peroxide (H2O2) production by 12-O-tetradecanoylphorbol-13-acetate (TPA)-activated HL-60 cells and superoxide anion (O2-) generation by xanthine/xanthine oxidase were compared. Of tested isoflavones, genistein is the most potent inhibitor among TPA-induced H2O2 formation by (dimethyl sulfoxide) DMSO-diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
214
1
12

Year Published

1997
1997
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 455 publications
(231 citation statements)
references
References 0 publications
4
214
1
12
Order By: Relevance
“…This triphenolic stilbene has been suggested as a potential chemopreventive agent based on its striking inhibitory effects on diverse cellular events associated with tumor initiation, promotion, and progression [39]. Resveratrol is an effective scavenger of superoxide and peroxynitrite radicals generated from enzymatic and nonenzymatic systems [120], and it exerts protective effects against DNA damage caused by hydrogen peroxide [3,27,41] and peroxynitrite [41]. Resveratrol also exerts a strong effect on superoxide radicals and hydrogen peroxide produced by macrophages stimulated by lipopolysaccharide (LPS) or phorbol ester.…”
Section: Resveratrolmentioning
confidence: 99%
“…This triphenolic stilbene has been suggested as a potential chemopreventive agent based on its striking inhibitory effects on diverse cellular events associated with tumor initiation, promotion, and progression [39]. Resveratrol is an effective scavenger of superoxide and peroxynitrite radicals generated from enzymatic and nonenzymatic systems [120], and it exerts protective effects against DNA damage caused by hydrogen peroxide [3,27,41] and peroxynitrite [41]. Resveratrol also exerts a strong effect on superoxide radicals and hydrogen peroxide produced by macrophages stimulated by lipopolysaccharide (LPS) or phorbol ester.…”
Section: Resveratrolmentioning
confidence: 99%
“…These compounds also inhibit the activity of a number of enzymes (Adlercreutz et al, 1993a;Evans et al, 1995;Makela et al, 1995a). Isoflavones have antioxidant activity (Wei et al, 1995), which in vivo has been shown to reduce the susceptibility of lipids to oxidation (Jenkins et al, 2000;Kapiotis et al, 1997;Ruiz-Larrea et al, 1997;Sheiber et al, 1999;Tikkanen et al, 1998) contributing to the overall cardio-protective effects of soy protein by favorably influencing lipid homeostasis (Anderson et al, 1995;Crouse et al, 1999).…”
mentioning
confidence: 99%
“…Genistein is also an inhibitor of DNA topoisomerase 82 , which may be an integral part of its differentiation-inducing properties. It is also an antioxidant 83 , and induces apoptosis in breast cancer cell lines in vitro 84 . Furthermore, genistein also has antiproliferative and antiangiogenic effects on vascular endothelial cells in vitro 85 , leading to the hypothesis that its antiangiogenic properties may be responsible for the relatively indolent nature of breast carcinomas in Asian women.…”
Section: Anticancer Mechanismsmentioning
confidence: 99%